2021
DOI: 10.1016/j.urology.2020.11.051
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of a Commercial Database on the Use of Erectile Dysfunction Treatments for Men With Employer-Sponsored Health Insurance

Abstract: OBJECTIVETo investigate the annual erectile dysfunction (ED) prevalence among men enrolled in an employer-sponsored health insurance (ESHI) plan and evaluate ED treatment profiles among those with an ED diagnosis. METHODSA cross-sectional claims analysis was conducted using the IBM MarketScan Commercial Database, a nationally representative sample of US workers enrolled in ESHI plans. Patients aged 18-64 with at least one ED medical diagnosis claim and continuous enrollment in a given year between 2009 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Previously published research also supports that men impacted by benefit exclusion have had limited access to ED treatment. 18 A commercial administrative claims analysis found that, although the annual prevalence of men with ESHI suffering from ED increased by 116% between 2009 and 2017, only 23% of men with an ED diagnosis received ED therapy paid for by their ESHI plan in 2017. 18 Furthermore, the proportion of men with ED undergoing PPI has declined in recent years (0.23% in 2009 to 0.11% in 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously published research also supports that men impacted by benefit exclusion have had limited access to ED treatment. 18 A commercial administrative claims analysis found that, although the annual prevalence of men with ESHI suffering from ED increased by 116% between 2009 and 2017, only 23% of men with an ED diagnosis received ED therapy paid for by their ESHI plan in 2017. 18 Furthermore, the proportion of men with ED undergoing PPI has declined in recent years (0.23% in 2009 to 0.11% in 2017).…”
Section: Discussionmentioning
confidence: 99%
“…18 A commercial administrative claims analysis found that, although the annual prevalence of men with ESHI suffering from ED increased by 116% between 2009 and 2017, only 23% of men with an ED diagnosis received ED therapy paid for by their ESHI plan in 2017. 18 Furthermore, the proportion of men with ED undergoing PPI has declined in recent years (0.23% in 2009 to 0.11% in 2017). 18 According to the AUA guideline for ED, patients should be informed of all treatment options, and the patient and the clinician together should determine the best course of therapy based on a discussion of the risks, benefits, and desired outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The 5% Medicare SAF data contains all site-of-service claims data of traditional Medicare fee-for-service beneficiaries in the United States, the majority of whom are aged >65 years. Relevant International Classification of Diseases, Tenth Revision, Clinical Modification diagnosis codes for ED from previously published literature, 23 including male erectile disorder (F52.21) and male ED unspecified (N52.9), were used to identify men with ED from the databases. This conservative calculation provided the estimate for the number of men with ED diagnosed by a health care provider who were seeking care for their ED symptoms with their provider.…”
Section: Methodsmentioning
confidence: 99%
“…This is of particular importance to Medicare and Employer-Sponsored prescription drug plans, many of which currently do not cover generic sildenafil. [22][23][24][25] This transition would lead to an improved care delivery model with substantial benefits, including a significant 'spillover effect' of increased continuity of care. A stable clinicianpatient relationship would better facilitate the management of hypertension, diabetes, cardiovascular disease, and cerebrovascular disease, all closely associated with ED.…”
mentioning
confidence: 99%